Responsibility as a Key Guarantee and a Special Role in the Practice of the Profession of an Attorney-at Law in Polish Law: Selected Issue - Białkowska, Paula (PRAWO i WIĘŹ, 2025)
The paper discusses the crucial role of professional self-governments in ensuring that attorneys do so properly, highlighting the significance of “public interest” in regulating and guiding their oversight in Polish law. This concept of the public interest serves a dual purpose: it sets the boundaries of supervision and defines the objectives of such supervision. The public corporation model is closely linked to this dual aspect of the public interest, resulting in the delegation of specific public tasks to professional self-governments. Focusing on the legal profession in Poland, the text looks at how it is held accountable for its actions.